LO039: The effect of desaturations on subsequent medical visits in infants discharged from the emergency department with bronchiolitis. (2nd June 2016) - Principi, T.; Coates, A.; Parkin, P.; Stephens, D.; DaSilva, Z.; Schuh, S.
Abstract : Introduction: Bronchiolitis is the most common lower respiratory tract infection among infants, characterized by wheeze and respiratory distress. Reliance on pulse oximetry has been associated with increased hospitalizations, prolonged hospital stay and escalation of care. The objectives were to determine if there is a difference in the proportion of unscheduled medical visits within 72 hours of emergency department discharge in infants with bronchiolitis who desaturate to <90% for at least one minute during home oximetry monitoring versus those without desaturations.Methods: This is a prospective cohort study from 2008 to 2013 enrolling 118 otherwise healthy infant aged 6 weeks to 12 months discharged home from a tertiary care pediatric emergency department with a diagnosis of acute bronchiolitis. The primary outcome was unscheduled medical visits for bronchiolitis, a visit to any health care provider due to concerns about respiratory symptoms, within 72 hours of discharge in infants with and without desaturations. Secondary outcomes included examination of the severity and duration of the desaturations, delayed hospitalizations within 72 hours of discharge and the effect of activity on desaturations.Results: During a mean monitoring period of 19 hours, 75/118 (64%) infants had at least one desaturation event (median continuous duration 3.4 minutes). 59/118 infants (50%) had at least 3 desaturations, 12 (10%) desaturated for >10% monitored time and 51(43%) had desaturations lasting ≥ 3 minutes continuously. 59/118 (50%) infants desaturated to ≤ 80% and 29 (24%) to ≤ 70% for ≥ 1 minute. A total 18/75 infants with desaturations (24.0%) had an unscheduled visit for bronchiolitis versus 11/43 of their non-desaturating counterparts (25.6%) [Difference - 1.6%; 95%CI -0.15 to ∞, p=0.66]. One of 75 desaturating infants (1.3%) and 2/43 (4.6%) of those without desaturations were hospitalized within 72 hours [Difference of -3.3%; 95% CI -0.04 to 0.10, p = 0.27]. Seventy seven percent of infants with desaturations experienced them during sleep or while feeding.Conclusion: The majority of infants with mild bronchiolitis experienced recurrent or sustained desaturations after discharge home. Children with and without desaturations had comparable rates of return for care, with no difference in unscheduled return medical visits and delayed hospitalizations.